An audit of physiotherapists' documentation on physical activity assessment, promotion and prescription to older adults attending out-patient rehabilitation. Issue 8 (10th April 2022) - Paim, Tatiana; Low-Choy, Nancy; Dorsch, Simone; Kuys, Suzanne
Abstract: Purpose: Identify if physiotherapists document the assessment, promotion and prescription of physical activity to older adults attending out-patient rehabilitation and assist them in the transition to an active lifestyle. Methods: An audit of physiotherapists' documentation in medical records of older adults who attended an out-patient rehabilitation program at a tertiary hospital. Results: Fifty-six medical records were reviewed. Mean age (SD) of participants was 79 (7) years. No documentation was found on the use of validated tools to assess physical activity levels of older adults. Prescription of physical activity was documented in 55/56 (98%) medical records. Seven (12.5%) medical records included documentation on goal setting regarding physical activity participation. Advice on regular physical activity post-discharge from the rehabilitation program was documented in 28/56 (50%) medical records. Formal referral to community-based physical activity programs was documented in 4/56 (7%) medical records. Conclusions: Evidence-practice gaps were found in physiotherapists' documentation of the promotion of physical activity to older adults attending out-patient rehabilitation, indicating a lack of assistance in the transition to an active lifestyle. These gaps were evident in the lack of; physical activity assessment, implementation of behaviour change strategies and formal referral to physical activity in the community post-discharge from out-patient rehabilitation. Implications for rehabilitation: Our findings suggest that physiotherapists are not widely applying evidence-based practice to promote physical activity to older adults attending out-patient rehabilitation nor supporting them in the transition to engage in physical activity in the community post-discharge from rehabilitation program. Incorporating physical activity assessment and behaviour change strategies into usual care may enable physiotherapists to successfully promote physical activity to older adults attending out-patient rehabilitation. Collaboration between the health care system and community-based physical activity programs is imperative to facilitate the sustainability of an active lifestyle after discharge from rehabilitation program.